Perancangan Aplikasi Rambu-Rambu Lalu Lintas Untuk Anak Usia Dini Berbasis Android Menggunakan CAI (Computer Assisted Intruction) - Tinambunan, Arnita; Ginting, Guidio Leonarde; Panjaitan, Melda (JURIKOM (Jurnal Riset Komputer), 2018)
Traffic signs are part of equipment - road safety which contains symbols serves to convey messages to road or traffic users as an effort to bring order, make it comfortable and safe for road users and the activities of those around them. Obeying traffic signs for traffic safety and order is very important to avoid accidents and violations of traffic regulations. Learning and awareness of the importance of traffic signs need to be instilled in the community from an early age, namely to children. Learning is a process or effort to create optimal learning conditions so that the competencies and learning objectives can be achieved. Computer-assisted learning or CAI (Computer Assisted Instruction) is one effective and efficient way of teaching and learning. Learning media must also be flexible. Examples of media in question are a device based on Android because it can be used en masse, easily accessible to anyone, and can be used in various places. Android is a system designed for touch screens mobile devices such as smartphones and tablet computers. With Android-based learning, users will be easier to understand, more interested and able to access material anytime and anywhere.